Decreased Tidal Volume With Increased Height, but not Colloid Transfusion, is Associated With Worse Outcomes and Postoperative Pneumonia After Coil Embolization of Aneurysmal Subarachnoid Hemorrhage: A Retrospective Study. Issue 4 (October 2018) - Zhang, Li-Min; Li, Rui; Zhao, Xiao-Chun; Wang, Ming-Li
ABSTRACT: Background: The tidal volume setting as well as colloid transfusion during the peri-operative period after intracranial aneurysm is controversial. A multicenter retrospective study was conducted to determine whether or not an increased tidal volume setting and colloid transfusion are associated with poor outcomes and postoperative pulmonary complications after intracranial aneurysm. Method: Data from endovascular coiling to treat intracranial aneurysms that took place between 30 March 2014 and 30 March 2016 were collected in a multicenter chart. The primary outcomes were better (defined as a Modified Rankin scores [MRS] ⩽2) and worse outcomes (MRS ≥3). Secondary outcomes included pneumonia and non-pneumonia in patients with intracranial aneurysms. Univariate analysis, bivariate logistic regression, Spearman correlation, and a linear regression model were performed to account for the association between peri-operative risk factors and different outcomes. Results: Bivariate logistic analysis showed that worse outcomes were correlated with height, Hunt and Hess scores (HHS), and Fisher grade ( P < 0.05). There was no significant association between colloid transfusion and worse outcomes and postoperative pneumonia ( P > 0.05). Postoperative pneumonia incidence was associated with increased height in a population with intracranial aneurysms ( P < 0.05). The Spearman correlation and a linear regression model suggested that increased height was significantly correlated with lower tidal volume setting (per unit of body weight; P < 0.05). Conclusion: Decreased tidal volume with increased height, but not colloid transfusion, was independently associated with worse outcomes and postoperative pneumonia across a spectrum of risk profiles. These findings may help to improve practice decisions regarding tidal volume settings.